Development and Validation of the College Social–Emotional Crossroads Inventory. (August 2020) - Garriott, Patton O.; Chao, Helen; Jessen, Mackenzie; Jordan, Ree Ae; Galluzzo, Joseph; Hadjeasgari, Courtney; Son, Yeji; Garza, Christina; Faris, Eve; Allan, Blake A.
The purpose of this study was to develop and provide initial validity evidence for the College Social–Emotional Crossroads Inventory (C-SECI). A sample (N = 751) of undergraduate students was randomly split into two samples for exploratory and confirmatory factor analysis. Results of exploratory factor analysis indicated that three factors should be extracted from the data and that the items comprised three subscales: Campus Cultural Fit, Academic Capital, and School–Family Integration. A confirmatory factor analysis suggested a bifactor structure was the best representation of the C-SECI items. Furthermore, scores on the C-SECI subscales correlated in expected directions with measures of institutional classism, academic self-efficacy, academic progress, global stress, first-generation college student status, subjective social status, and family income. The C-SECI is a brief measure that can be used to capture tensions students may experience between their postsecondary institutions and families and communities of origin.